(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In today’s world, when technology is reaching its pinnacle, there is no need for humans to do everything they can to ensure their existence. Humans are not need to carry big loads and deal with the repercussions, such as backbone injuries, etc. These are the minor functions that extraterrestrials, particularly Robots, can do. Swarm Robots is a game in which you control a swarm of robots.Swarm Robotics is a new technology that is still in the early stages of development. Working in a group is referred to as "swarming." Our team of four robots consists of a master and three other robots. The two categories that are generally used to classify robots are carrier and explorer. First, the explorer robots cover the whole route from point A to point B. They relay terrain data tothe carrier robots, and they respond in like. As a result, the slave works in accordance with the master’s instructions. They are constructed in such a manner that they may be used in even the most difficult terrains. As a result, the activities are completed quickly and effectively.